E-Learning in Higher Education: Challenges and Solutions - Yuliani (Journal of Research in Business, Economics, and Education, 2020)
The Covid 19 pandemic that has hit the world has changed many ways of life. Education is one of the sectors affected by this pandemic. Learning, which has been carried out directly through face-to-face, has switched to online E-Learning to prevent the expansion of the COVID-19 pandemic. Universities face a number of challenges in implementing E-Learning. This study aims to identify the factors that become obstacles in the implementation of E-Learning and strategies that can be applied to overcome the inhibiting factors of E-Learning. These challenges come from the human aspect, technical aspects, financing, E-Learning content. For this reason, universities must prepare strategic steps so that obstacles or challenges do not affect the quality of learning that occurs between lecturers and students.